SUSTAINABILITY OF DIGITAL BUSINESS. ADVANTAGES OF ADOPTION OF BUSINESS MODELS BASED ON THE DIGITAL ECONOMY - Gafencu, Nicoleta Larisa (Ecoforum Journal, 2023)
In the digital age, technological transformation is associated with organizational performance, economic growth, environmental protection, and social welfare, being an integral part of the business model. Innovation is no longer just an element of the product created by the company, the way we create the product, can represent the created product itself. Large companies in the market for the last 30 years are companies creating digital products. Adopting the latest technologies is imperative for companies for which the main purpose is to remain or become competitive. The widespread implementation of digital solutions will contribute to sustainable development. Regarding the adoption of technology, it is certain that organizations embrace the implementation of digital tools, but the question that arises and which we want to answer through this study concerns the benefits of their use for the environment and society.